The Role of Lipid Profile as an Independent Predictor of Non-alcoholic Steatosis and Steatohepatitis in Morbidly Obese Patients - Ganjooei, Narges Ashraf; Jamialahmadi, Tannaz; Nematy, Mohsen; Jangjoo, Ali; Goshayeshi, Ladan; Khadem-Rezaiyan, Majid; Reiner, Željko; Alidadi, Mona; Markin, Alexander M.; Sahebkar, Amirhossein (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Obesity is globally one of the major health problems worldwide. Morbid obesity (body mass index (BMI) > 40 kg/m2 or over 35 with a comorbidity) is associated, apart from other diseases, with an increased risk of non-alcoholic fatty liver disease (NAFLD). Moreover, dyslipidemia is an important comorbidity that is frequently found in NAFLD patients. The aim of this study was to analyze whether serum lipids in morbidly obese patients are associated with the spectrum of NAFLD. Methods: Total serum cholesterol, LDL-cholesterol, HDL-cholesterol, non-HDL cholesterol, VLDL and triglycerides were analyzed in 90 morbidly obese patients. The association of lipid profile parameters with histopathological, elastographic and sonographic indices of NAFLD, nonalcoholic steatohepatitis (NASH) and liver fibrosis were explored. Results: The mean levels of serum total cholesterol, LDL-C and non-HDL cholesterol in patients with positive histology for liver steatosis and NASH were significantly higher than patients with negative histology. None of the indices showed a strong association with NAFLD, NASH or liver fibrosis after adjustment for potential confounders. Conclusion: slight predictive value of lipid profile is not sufficiently enough to use solely as a noninvasive test in predicting NASH or liver fibrosis.